ARTIKEL REVIEW : MANFAAT KANDUNGAN ALFA-MANGOSTIN DALAM KULIT BUAH MANGGIS - Restu Hidayanti (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2024)
Mangosteen, as one of the most popular tropical fruits in Indonesia, has many chemical compounds in its rind that are beneficial for treatment. Alpha-mangostin which is a major component has various activities such as antibacterial, anticancer, and antitumor. Mangosteen peel has the main compound, xanthone. Where there is an important content in inhibiting the growth of cancer cells, and anti-inflammation. In addition, mangosteen peel also has anti-inflammatory compounds such as flavonoids, vitamins B1, B2, C, saponins and tannins which have properties in accelerating healing. In fact, mangosteen peels are used medicinally by Asian populations in the treatment of skin infections and cholera since ancient times. The main and most abundant constituent found in Garcinia mangostana L, the xanthone class is α- mangostin. One of the main compounds in mangosteen pericarp is α- Mangostin. α- Mangostin shows good pharmacological activity as well as from in vivo or in vitro models. α- Mangostin shows strong potential to be used as a drug in the future. However, the application of α-Mangostin in the clinical field is still lacking.